Nickel-catalyzed borrowing hydrogen annulations: access to diversified N-heterocycles. Issue 54 (19th June 2019) - Yang, Peng; Zhang, Caili; Gao, Wen-Chao; Ma, Yu; Wang, Xiuhua; Zhang, Li; Yue, Jieyu; Tang, Bo
Abstract : An efficient nickel-catalyzed synthesis of diversified N-heterocycles via atom-economic borrowing hydrogen annulations of easily available alcohols and amines. Abstract : Herein, we report an efficient nickel-catalyzed direct cyclization of amines with alcohols for the synthesis of various nitrogen containing heterocycles. These processes employ the sustainable "borrowing hydrogen" strategy and have many advantages, such as earth-abundant metal catalysts, easily available starting materials, wide synthetic versatility and harmless waste emission.